Menyingkap Tabir dari Dalam Diri: Pergulatan Manusia Atas Kesadaran Dalam Pengalaman Mistis Sufi dan Fenomenologi Husserlian - Zahrotul Faridah; Suadi Saad; Sholahuddin Al Ayubi (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
Sufism, as a tradition of Islamic mysticism, places the human spiritual journey at the core of the divine quest. This article focuses on the experience of Baqa, the continuity of consciousness after the annihilation of the Fana self. As a phenomenon that can be analyzed through Husserl's Epoche method, which suspends empirical worldly assumptions to reveal the pure structure of consciousness. The main argument is that Baqa and Epoche have parallel phenomenological structures, both requiring self-suspension so that deeper realities can be authentically present. This study aims to examine how Husserl's phenomenological framework can function as an analytical instrument to understand Sufi mystical experience in the context of contemporary Muslim thought. Using a qualitative approach based on a literature review (Library Research), this study integrates three analytical perspectives: the hermeneutics of classical Sufi texts, the psychology of spiritual experience, and a socio-anthropological examination of Mysticism as a cultural phenomenon. These findings demonstrate that the Husserlian Phenomenological approach is not only methodologically relevant, but opens up new epistemic spaces for contemporary Muslim thought to critically and transformatively reflect on its Sufi spiritual heritage. Keywords: Baqa, Epoche and Sufism